Determinants of Integrated Reporting Disclosure in Indonesian Companies: Faktor-faktor yang Mempengaruhi Pengungkapan Laporan Terpadu di Perusahaan-Perusahaan Indonesia - Mutala’liah, Lili’; Nurasik, Nurasik (Indonesian Journal of Law and Economics Review, 2025)
Background: Integrated reporting has become an essential element of corporate transparency and accountability in the modern business environment. Specific Background: In Indonesia, the implementation of integrated reporting among non-financial companies remains relatively limited despite growing awareness of sustainability disclosure. Knowledge Gap: Previous studies have not sufficiently explained the influence of institutional ownership, firm size, and profitability on the extent of integrated reporting. Aims: This study aims to examine the determinants of integrated reporting disclosure in companies listed on the Indonesia Stock Exchange. Results: The findings show that firm size and profitability significantly influence integrated reporting disclosure, while other variables such as institutional ownership show no significant impact. Novelty: The study provides empirical evidence on integrated reporting practices within the Indonesian context. Implications: These results can assist regulators and companies in improving transparency and aligning corporate reporting with sustainability principles. Highlights:• Examines the determinants of integrated reporting disclosure in Indonesian companies.• Shows firm size and profitability significantly influence disclosure levels.• Provides empirical evidence for improving transparency and accountability. Keywords: Integrated Reporting, Firm Size, Profitability, Institutional Ownership, Sustainability Disclosure